Performance of Treated Date Palm Leaf Fiber as a Sustainable Reinforcement for Different Soil - Al-Hassnawi, Noor S.; Azmi, Mastura; Fattah, Mohammed Y.; Ahmad, Fauziah (Civil Engineering Journal, 2024)
The use of sustainable materials in geotechnical applications has increased in recent years due to their positive impacts on geo-environmental and future generations. This paper contributes to existing knowledge on geocell reinforcement of soil by proposing a new inexpensive product: cells made from natural materials, Date Palm Leaf fiber coated with Bitumen (DPLB), to improve its durability, as an alternative to commercially available high-density polyethylene (HDPE) geocells. A physical laboratory model was designed to examine the performance of the DPLB cell and HDPE cell reinforced base layer under repeated loading. The study tested different infill materials gravel, sand, and recycled asphalt pavement (RAP) in DPLB cells and HDPLE geocell-reinforced granular layers and compared them to unreinforced layers. The reinforcement's performance was assessed using elastic deformation, permanent deformation, traffic benefit ratio, and rut depth reduction. Results showed that both DPLB cell and geocell reinforced sand decreased the cumulative permanent deformations compared to the unreinforced layer. DPLB reinforcement cells improved the permanent deformation behavior by 30% due to the lateral restriction provided by the DPLB pockets on the infill materials, while the geocell improved it by 7%. The traffic benefit ratio (TBR) of geocell-reinforced RAP is 26% greater than that of the DPLB cell-reinforced RAP section, although both geocell and DPLB cell exhibited similar TBR values in the case of gravel infill materials. The experimental results showed that DPLB cells are a cost-effective and environmentally friendly substitute for commercially available HDPE geocells in soil reinforcement applications. Doi: 10.28991/CEJ-2024-010-10-018 Full Text: PDF